Treatment of Ipilimumab Induced Graves' Disease in a Patient with Metastatic Melanoma. (11th January 2016) - Azmat, Umal; Liebner, David; Joehlin-Price, Amy; Agrawal, Amit; Nabhan, Fadi
Abstract : Objective . Thyroid disease has been reported among the endocrinopathies that can occur after treatment with ipilimumab. Graves' disease, however, has been rarely reported with this medication. Here we report a case of Graves' disease diagnosed after initiation of ipilimumab in a patient with melanoma. Methods . We present the clinical presentation and management course of this patient followed by a related literature review. Results . A 67-year-old male with metastatic melanoma was started on ipilimumab. He developed hyperthyroidism after two doses of ipilimumab. The cause of hyperthyroidism was determined to be Graves' disease. Ipilimumab was held and the patient was started on methimazole with return to euthyroid status. Ipilimumab was resumed and the patient continued methimazole during the course of ipilimumab therapy, with controlled hyperthyroidism. Restaging studies following four cycles of ipilimumab showed complete response in the lungs, with residual melanoma in the neck. The patient then underwent total thyroidectomy and left neck dissection as a definitive treatment for both hyperthyroidism and residual melanoma. Conclusion . Graves' disease can develop after starting ipilimumab and methimazole can be an effective treatment. For patients whose hyperthyroidism is well-controlled on methimazole, ipilimumab may be resumed with close monitoring.